Penampilan Vegetatif Tanaman Kubis Bunga (Brassica Oleracea Var. Botrytis) Kultivar PM 126 F1 Akibat Pemberian Pupuk Organik Limbah Sludge Kertas Dengan Pupuk Nitrogen - Ainun Azizah; Elia Azizah; Rika Yayu Agustini (Jurnal Ilmiah Wahana Pendidikan, 2021)
The research was carried out in the experimental field of the Faculty of Agriculture, Singaperbangsa Karawang University, which is located in Pasirjengkol Village, Majalaya District, Karawang Regency, West Java Province. The research method with a single factor Randomized Block Design (RBD). There were 10 treatmet combinations and repeated 3 times. The result of this experiment showed that the combination of paper sludge waste organic fertilizer and nitrogen fertilizer had a significant effect on growth components (plant height, number of leaves, leaf area, and root length). The highest yield on plant height was the combination of C (3 ton/ha organic fertilizer waste paper sludge + 100 kg/ha of nitrogen fertilizer) of 12.67 cm, the number of leaves in combination C (3 ton/ha organic fertilizer waste paper sludge + 100 kg/ha of nitrogen fertilizer) amounted to 12.08 strands, and leaf area on a combination of C (3 ton/ha organic fertilizer waste paper sludge + 100 kg/ha nitrogen fertilizer) of 51.75 cm2.